Extração, caracterização e aplicação do óleo essencial e extrato bruto da casca de laranja pera na congelação de espermatozoides epididimários bovinos - Brilhante, Christianne Emmanuelle Andrade Pires (2022)
Brazil has the largest commercial cattle herd, and with that, there is a need to increasingly improve the performance of the processes involved in this area. For this, biotechniques applied to reproduction, such as criopreservation, are used. Seeking to avoid the damage caused by this technique, seminal extenders are used. However, standard extenders that are commonly used contain ingredients of animal source, such as egg yolk and milk. These ingredients are difficult to maintain a standard production and they increase the risk of contamination. That being said, there is a great interest in the development of extenders with a plant source. Orange is a fruit rich in secondary metabolites, such as carbohydrates and phenolic compounds, and these are related to its antioxidant activity. In Brazil, the sweet orange (Citrus sinensis (L.) Osbeck) is the most important citrus variety and its use by the juice industry generates tons of agricultural waste, mainly from its peel. This work had the intention to give an alternative use for the orange peel, acting as raw material for the production of its extract and essential oil. These can be beneficial within the formulation of a seminal extender as they show antimicrobial antioxidant characteristics. Therefore, this work aimed to evaluate the use of orange peel extract and essential oil for the production of a new extender with activity in the sperm cryopreservation. The essential oil extraction, its chemical composition and antioxidant potential characterization were performed. Different essential oil nanoemulsions were formulated, and these were tested in order to evaluate their protective potential epididymal sperm cells. The extraction of the crude extract of the orange peel was also performed, this was elaborated regarding its phytochemical composition, antioxidant potential and antimicrobial potential. These extenders were tested, with and without the presence of egg yolk, with the addition of 10 and 20% extract. The results showed that the essential oil did not show an antioxidant potential, as well as it was not successful in protecting the sperm cells. As for the extract, it showed antioxidant potential by the DPPH method, however, sperm parameters evaluated showed that there was no significant difference between the standard extender with the added extract and the standard extender alone. Based on these results, it can be concluded that the orange peel extract should be better evaluated for its cryoprotective potential.